2000
DOI: 10.1165/ajrcmb.22.2.3674
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Mapping of Ozone-Induced Acute Cytotoxicity in Tracheobronchial Airways of Isolated Perfused Rat Lung

Abstract: Acute lung injury induced by reactive oxygen gases such as ozone (O(3)) is focal and site-selective. To define patterns of acute epithelial injury along intrapulmonary airways, we developed a new analytic approach incorporating labeling of permeable cells, airway microdissection, and laser scanning confocal microscopy, and applied it to isolated perfused rat lungs where ventilation and breathing pattern could be controlled. After exposure to O(3) (0, 0.25, 0.5, or 1.0 ppm), lungs were lavaged to assess lactate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 28 publications
3
34
0
Order By: Relevance
“…Previous studies have adapted EH-1 for use on microdissected airways and demonstrated it to be a reliable probe for cells undergoing necrosis [43]. Intraperitoneal injection of NA resulted in a marked increase in EH-1-permeable Clara cells by 6 h after injection in Swiss Webster mice [29], and 12 h after injection in C57BL/6 mice in the present study, indicating that NA-induced exfoliation of Clara cells was due to necrosis.…”
Section: Kgf Protects Against Acute Airway Injury Aö Yildirim Et Alsupporting
confidence: 67%
“…Previous studies have adapted EH-1 for use on microdissected airways and demonstrated it to be a reliable probe for cells undergoing necrosis [43]. Intraperitoneal injection of NA resulted in a marked increase in EH-1-permeable Clara cells by 6 h after injection in Swiss Webster mice [29], and 12 h after injection in C57BL/6 mice in the present study, indicating that NA-induced exfoliation of Clara cells was due to necrosis.…”
Section: Kgf Protects Against Acute Airway Injury Aö Yildirim Et Alsupporting
confidence: 67%
“…In microscopy, a "disector" is used as a volume probe (Sterio, 1984). The disector approach can be used with thick sections and viewed with a brightfield or laser confocal microscopes that optically focus through the section (Figure 7) (Postlethwait et al, 2000). The usual section thickness is 30 to 50 µm and a short depth of focus (usually about 1 µm) is essential to optically section the tissue.…”
Section: Numbermentioning
confidence: 99%
“…More efficient design-based methods for estimation of cell numbers are now available using a ''disector'' [107]. These are used widely to provide accurate estimates of cell numbers during injury and repair of conducting and distal airways [108,109]. These methods are critical because, as illustrated in table 6, profile counts are not equivalent to number counts in three-dimensional volume and should be avoided as an endpoint because of their inherent bias.…”
Section: Bronchial Vasculaturementioning
confidence: 99%
“…These methods are critical because, as illustrated in table 6, profile counts are not equivalent to number counts in three-dimensional volume and should be avoided as an endpoint because of their inherent bias. The disector approach can be used with thick sections and viewed with a brightfield or laser confocal microscope that optically focuses through the section [109]. The usual section thickness is 30-50 mm and a short depth of focus (usually ,1 mm) is essential to optically section the tissue using a light microscope.…”
Section: Bronchial Vasculaturementioning
confidence: 99%